Translation Procedures of Political Terms in Book Entitled A Magic Gecko: Cia’s Role Behind the Fall of Soekarno - Ni Made Dwi Jayanthi; Ni luh Nyoman Seri Malini (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2020)
This research intends to investigate the translation procedures of political terms of a book entitled A Magic Gecko: CIA’S Role behind the Fall of Soekarno written by Geerken (2009) and translated by Adiati (2011). The data was collected by observation and note-taking techniques. Political terms in the forms of words, phrases,and expression are the data in this article which was then analyzed through qualitative research method. The grand theory proposed by Newmark (1988) was applied to analyze procedures of translation of the book. The findings show that there were eight out of eighteen translation procedures applied in translating political terms in the book Magic Gecko. The translation procedures were literal translation, transference, naturalization, descriptive equivalent, through-translation, shift, reduction and expansion, and couplet